EFEKTIVITAS PROBLEM BASED LEARNING BERBASIS ETNOMATEMATIKA UNTUK MENINGKATKAN KEMAMPUAN PEMECAHAN MASALAH MATEMATIS - Rekha Gayatri Putri; Ilmiyati Rahayu; Yani Setiani (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study aimed to determine the effectiveness of Ethnomathematics-based Problem Based Learning (PBL) in improving students’ mathematical problem-solving ability on curved-side solid geometry. A quantitative quasi-experimental design using a non-equivalent pre-test post-test control group was employed. The subjects were eighth-grade students of MTs Al-Hamidiyah. The results showed that the experimental class achieved a higher posttest mean score (87.22) than the control class (80.11). Hypothesis testing showed p < 0.001, indicating a significant difference. The N-Gain of the experimental class was 76.45% (high), while the control class was 63.34% (moderate).